English Learning Strategies for Vocabulary Mastery - Bambang Purwanto, Muhammad; Hidayad, Ferri (English Education:Journal of English Teaching and Research, 2022)
This study intends to identify the categories of English vocabulary learning procedures that high school students most frequently employed. The idea of language learning techniques from Rebecca L. Oxford was used to analyze the use of English vocabulary acquisition strategies. Both qualitative and quantitative methods were used in this study. For learners in vocational schools, the qualitative technique is utilized to describe vocabulary acquisition strategies. Data on the prevalence of various English vocabulary acquisition methodologies for high school pupils are presented using the quantitative method. The Class 11 of Hospitality Students academic year 2021 SMK Telenika Palembang served as the study's data sources, and the information was gathered from the answers to questionnaires that the students had completed. The analysis found that pupils frequently use memory to learn English vocabulary. Then, the social technique is the second most often used strategy among pupils. The third technique chosen by students is the cognitive one. The fourth strategy is Compensation, followed by the fifth strategy, Metacognitive. The affective approach is the one students employ most often when acquiring English vocabulary.